OBSERVATION OF INTERMOLECULAR LIGAND-EXCHANGE IN LEAD(IV) CARBOXYLATES BY 1-D AND 2-D PB-207 NMR-SPECTROSCOPY - Buston, J; Claridge, T; Moloney, M (1995)
Intermolecular ligand exchange, which is slow on the NMR timescale, has been observed for lead(IV) carboxylate species containing acetate and benzoate ligands by the use of 207Pb NMR spectroscopy.